The Volatility of Oil Wealth under Uncertainty about Parameter Values - Kjell Arne Brekke; Pål Børing (Statistics Norway, Research Department, 1994)
Aslaksen et al. (1990) concluded that the petroleum wealth of Norway, and hence the permanent income from petroleum extraction, was as uncertain as the yearly oil revenues. Their conclusion was based on wealth estimates using official price projections, with no independent empirical analysis of the oil price process. In this paper the wealth estimates are based on an empirical analysis of the oil prices. We find that the best estimate of the roots of the price process indicates a more stable wealth than the conclusions in Aslaksen et al. (1990) indicated. If we introduce a possible shift in the price process at the time of OPEC I in 1974, the price shift in OPEC II, has an indirect effect on petroleum wealth through its influence on the best parameter estimate. This indirect effect is considerable, and the main conclusions from Aslaksen et al. (1990) are maintained in spite of the low roots.
Keywords: H60; Q30; 330; Resource wealth; Parameter uncertainty.